Meta-Analysis: The Effect of Teaching Media towards Students English Vocabulary Mastery - Yudiramanda, Shofiyah Dinda; Suhandoko, Farsya Shabira; Sulhan, Muhammad (JEdu: Journal of English Education, 2024)
This study conducts a meta-analysis to evaluate how different teaching media affect students' English vocabulary mastery. This research uses a quantitative method by conducting meta-analysis to review 20 quantitative experimental articles published between 2018 and 2024. The research aims to give a detailed understanding of the impact of various media on vocabulary learning. The study finds that interactive and engaging media, such as games, songs, and applications like Duolingo and "My Dictionary," significantly improve vocabulary mastery. The Guessing Game shows the highest impact with an effect size of 0.893, indicating a huge effect, while the Mesmerize Application has the least impact with an effect size of 0.005. The results show that elementary and junior high school students benefit the most from these media, with the highest effect sizes at these educational levels. The findings support the use of innovative teaching media in English language education, emphasizing student-centered learning and the use of technology to enhance educational outcomes. This research provides important insights for educators, curriculum developers, and policymakers looking to improve English vocabulary teaching strategies. It advocates for the strategic use of engaging teaching methods and technology to support vocabulary mastery, which is crucial for effective communication skills in English.